Mucormycosis in diabetes mellitus - Khatiwada, Prashant; Giri, Aditi; Khatiwoda, Prasana (Journal of Advances in Internal Medicine, 2012)
Mucormycosis is an opportunistic fulminant fungal infection, which mainly infects immunocompromised patients. Infection with mucormycosis can cause devastating rhino-orbital-cerebral and pulmonary infection with an extremely poor prognosis. The infection begins in the nose and paranasal sinuses due to inhalation of fungal spores. We report a case of mucormycosis in an uncontrolled diabetic patient to emphasize early diagnosis of this potentially fatal fungal infection. Rhino-orbitalcerebral mucormycosis is the most common manifestation in patients with diabetes mellitus. We also review the current concepts in management of mucormycosis. Mucormycosis remains difficult to treat and requires a multifaceted approach involving elimination of predisposing factors, surgical debridement, and anti-fungal therapy. Lipid formulations of Amphotericin B are the treatments of choice. DOI: http://dx.doi.org/10.3126/jaim.v1i2.6531 Journal of Advances in Internal Medicine 2012;01(02):73-75